Gemcitabine-induced Gli-dependent activation of hedgehog pathway resists to the treatment of urothelial carcinoma cells. - Yu-Hao Chang; Hoi-Lam Tam; Meng-Chien Lu; Huei-Sheng Huang (PLoS ONE)
Patients with urothelial carcinoma (UC) experience gemcitabine resistance is a critical issue. The role of hedgehog pathway in the problem was explored. The expressions of phospho-AKTser473, phospho-GSK3βser9 and Gli2 were up-regulated in gemcitabine-resistant NTUB1 (NGR) cells. Without hedgehog ligands, Gli proteins can be phosphorylated by GSK3β kinase to inhibit their downstream regulations. Furthermore, the GSK3β kinase can be phosphorylated by AKT at its Ser9 residue to become an inactive kinase. Therefore, overexpression of AKT1, Flag-GSKS9D (constitutively inactive form) or active Gli2 (GLI2ΔN) in NTUB1 cells could activate Gli2 pathway to enhance migration/invasion ability and increase gemcitabine resistance, respectively. Conversely, overexpression of Flag-GSKS9A (constitutively active form) or knockdown of Gli2 could suppress Gli2 pathway, and then reduce gemcitabine resistance in NGR cells. Therefore, we suggest gemcitabine-activated AKT/GSK3β pathway can elicit Gli2 activity, which leads to enhanced migration/invasion ability and resistance to gemcitabine therapy in UC patients. The non-canonical hedgehog pathway should be evaluated in the therapy to benefit UC patients.